2019
DOI: 10.1007/s42250-019-00054-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Chemical Composition and Antioxidant Capacity of Extracts from Crataegus azarolus L.: Effect of Growing Location of an Important Tunisian Medicinal Plant

Abstract: For the first time, the current study was designed to evaluate growing location on the chemical composition as well as the DPPH capacity of Crataegus azarolus L. (var. aronia (Willd.) Batt.) methanolic aqueous extracts. It was found that Crataegus azarolus L. collected from Neber (Governorate of Kef) had the highest total phenolic, flavonoids, condensed and hydrolysable tannin contents while the same genus growing in Jdidi (Governorate of Zaghouan) were characterized by the highest content of sugar (15.27 mg G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Total Phenol content (TPC) was determined according to the Folin-Ciocalteu method as described before by Yahyaoui (p) Solid to liquid ratio (g/mL) 5 7.5 10 et al [14] with some modification. Briefly, 300 μL sample of extract diluted in methanol (2 mg/5 mL) were added to 1.5 mL of Folin-Ciocalteu reagent (10/100).…”
Section: Determination Of Total Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total Phenol content (TPC) was determined according to the Folin-Ciocalteu method as described before by Yahyaoui (p) Solid to liquid ratio (g/mL) 5 7.5 10 et al [14] with some modification. Briefly, 300 μL sample of extract diluted in methanol (2 mg/5 mL) were added to 1.5 mL of Folin-Ciocalteu reagent (10/100).…”
Section: Determination Of Total Phenolicsmentioning
confidence: 99%
“…Antiradical activity was evaluated using 1, 1-diphenyl-2-picrylhydrazyl free radical (DPPH) with some modifications [14,15]. Aliquots (1.5 mL) of various dilutions of (1) C = 8.9321A + 0.0102 r 2 = 0.9987…”
Section: Antiradical Activitymentioning
confidence: 99%
“…Previous studies revealed that the leaves, flowers, and fruits of C. azarolus had various biological activities including antimicrobial, antioxidant, antihyperglycemic, and antihyperlipidemic activities [15,16]. These potential health benefits are related to their high content in many natural active compounds, such as flavonoids, minerals, sugar alcohols, carotenoids, polyphenols, amino acids, and tannins [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…The extract was filtered through Whatman no. 4 paper and then stored at −21°C until further use (Yahyaoui et al., 2019).…”
Section: Methodsmentioning
confidence: 99%